Air-assistance in spray booms which have different spray volumes and nozzle types for chemically controlling spodoptera frugiperda on corn - Gimenes, Marcelo [UNESP]; Raetano, Carlos [UNESP]; Dal Pogetto, Mário [UNESP]; Prado, Evandro [UNESP]; De Souza Christovam, Rafael [UNESP]; Rezende, Denise [UNESP]; De Almeida Costa, Saulo [UNESP] (My University, 2012)
The study aimed to evaluate the performance of air assistance in spray booms using different types of nozzles and spray volumes. We took into account spray deposits, fall armyworm control and crop corn performance in a narrow row cropping system. The experiment was carried out at the experimental area of Sao Paulo State University, Botucatu/SP, Brazil, during the 2008/2009 agricultural season, in randomized blocks with a factorial scheme (2×2+1) and four replications. Two spray nozzles (flat fan nozzle and hollow cone nozzle) were tested, combined with two air assistance levels in the spray boom (with and without air assistance) and a treatment control. In the experimental spraying, Spinosad insecticide was sprayed in amounts of 48 g active substance (a.s.)/ha. The air assistance in the spray boom increased the spray deposits in the V 4 growth stage of the corn plants. Moreover, the application of this technology showed higher efficiency on fall armyworm control, reaching a 100% level 15 days after spraying, in the V 10 growth stage of the plants. The hollow cone nozzle increased the spray deposit level on the corn plants compared with the flat fan nozzle, at growth stage V 4. However, the flat fan nozzle, combined with air assistance technology, was more effective for controlling fall armyworm in the same growth stage (V 4), although the hollow cone nozzle increased the deposit levels on the plants. All the technologies tested in the study promoted a reduction of plant damage from fall armyworm attack. Corn productivity is directly related to the control efficiency of fall armyworm.
Keywords: biological efficacy; nozzles; spray volume; spraying technique; Zea mays; Spodoptera frugiperda